Pengaruh Jenis dan Tingkat Kerapatan Gulma Terhadap Pertumbuhan dan Produksi Tanaman Sorgum (Sorghum Bicolor L.) - Anggeraini, Dita; Sembodo, Dad R.J.; Sunyoto, Sunyoto (Politeknik Negeri Lampung., 2016)
Sorghum is one of serealia plants that have a big potential to be developed. Sorghum is beneficial as a source of food, animal feed, as well as various industrial raw materials. Sorghum is potential to be developed with the application of proper cultivation, one of them is optimal maintenance. The lack of maintenance cause low production. One of maintenance is weed control. Weeds can create a competition with cultivation plants to fight means growing. Type and weed density are influence growth a development of sorghum. The purpose of this research is to know: (1) The influence of type of weeds to growth and production of sorghum plants, (2) The influence of weeds density to growth and production of sorghum plant, and (3) There is interaction between type and weeds density when influence the growth of weeds, also growth and production of sorghum plants. This research is done in South Lampung and weeds laboratory University of Lampung on December 2014 - April 2015. Treatments arranged in a factorial strip plot design with three replications. The first factor is three types of weeds, that are Asystasia gangetica, Cyperus rotundus, and Rottboelia exaltata. The second factor is density 0, 10, 20, 40, and 80 weeds/m2. If assumption are met, the data is analyzed by using variance analysis and followed by a least significant difference (LSD) 5%. The result shows: (1) The type of weeds influence growth and yield component of plant height and steam diameter 3 WAP, fresh weight and dry stover, also weight of 100 grains on water content) WC14%, (2) The density of 80 weeds/m2 influence the height a plant 3 and 9 WAP, number of leaves 6 MST, steam diameter 3, 6, and 9 WAP, weight of fresh stover plant, weight of 100 grains on water content 14%, weight of sorghum seed, and (3) There is no interaction between the type and weeds density when influence growth and sorghum production, but there is interaction when influence the growth of weeds. Keyword: sorghum, weeds, competition